System of demonstration programs and Control knowledge in the integrated training environment “Bases of algorithmization and programming” - Kolesnikova Н.В.; Nadeeva А.В. (Journal of Information Technologies in Education (ITE), 2007)
Setting of environment of demonstration of the programs is described, the use of which allows to spare more of attention of exactly analysis of algorithms and current and final checking of knowledges system, which includes both the traditional system of tests and module of testing of programmatic code, that is specific for this subject domain.